COVID-19 in children with cancer: a review of case reports - Muhd Helmi, Muhd Alwi; Taib, Fahisham; Nik Yusoff, Nik Khairulddin; Nasir, Ariffin; Mohamad, Norsarwany (Faculty of Medicine and Health Sciences, 2020)
Introduction: Immunosuppressed individuals and paediatric population are susceptible to infections. This case report depicts the presentation and severity of COVID-19 infection in a single case report of a Leukemic child on chemotherapy and compares the course of disease with previously reported case reports of immunocompromised children with COVID-19. Case presentation: We reported a 27-month-old boy, known case of B-cell Acute Lymphoblastic Leukemia in remission, which was infected with COVID-19. Our reported case was asymptomatic and recovered well without developing any complication related to COVID-19 infection despite being immunocompromised. A comparison made with published case reports of immunocompromised children with COVID-19 revealed variability in the presentations whereby most of the children were mildly affected. Other factors such as concomitant infection, the severity of immunosuppression, presence of other co-morbidities and infection by different virus subtypes may explain the variability in the severity of COVID-19 infection. Conclusion: Mild presentation of COVID-19 in immunocompromised children can be explained by the lack of overwhelming immune responses toward SARS-CoV-2 virus in an immunocompromised host. Clinicians, however, have to be vigilant as immunocompromised children can be severely affected by COVID-19. Further studies on the pathophysiology of COVID-19 infection in immunocompromised hosts and factors contributing to variability of presentations among patients with similar immune responses are required before a firm conclusion can be made